Inheritance of Resistance to the Bacillus thuringiensis Toxin Cry1C in the Diamondback Moth - Liu, Y. (1997)
Laboratory selection increased resistance to the Bacillus thuringiensis toxin Cry1C in a strain of diamondback moth (Plutella xylostella). The selected strain was derived from a field population that had evolved high levels of resistance to Bacillus thuringiensis subsp. kurstaki and moderate resistance to Cry1C. Relative to the responses of a susceptible strain of diamondback moth, the resistance to Cry1C of the selected strain increased to 62-fold after six generations of selection. The realized heritability of resistance was 0.10. Analysis of F(inf1) hybrid progeny from reciprocal crosses between the selected strain and a susceptible strain showed that resistance to Cry1C was autosomally inherited. The dominance of resistance to Cry1C depended on the concentration; inheritance was increasingly dominant as the concentration decreased. Responses of progeny from single-pair families showed that resistance to Cry1C and resistance to Cry1Ab were inherited independently, which enhances opportunities for managing resistance. However, compared with projections based on previously reported recessive inheritance of resistance to Cry1A toxins, the potentially dominant inheritance of resistance to Cry1C observed here could accelerate evolution of resistance.